Peranan Free Living Amoeba - Achantamoeba sebagai patogen penyebab kelainan pada otak dan mata - Ryan Halleyantoro; Ika Puspa Sari (JURNAL KEDOKTERAN RAFLESIA, 2021)
The free-living amoeba (FLA) group of protozoa that can be found in various types of conditions in nature, one of which is the genus Acanthamoeba. Although, the number of infections caused by this protozoan is low, the diagnosis was still difficult to confirm and therefore there were a higher mortality, especially those associated with encephalitis. This review presents some information about the biology, pathogenesis, clinical symptoms caused by Acanthamoeba in humans, as well as diagnostic and therapeutic methods. Acanthamoeba infection in humans can cause disorders such as granulomatous amoebic encephalitis (GAE), acanthamoeba keratitis and cutaneous acanthamoeba. In addition, this parasite can also act as a vector of pathogens.